Effect of Active Leg Stretching on Foot Sensitivity in Type 2 Diabetes Mellitus Patients at Tilongkabila Health Center - Rahma Aulia Mansur; Ita Sulistiani; Gusti Pandi Liputo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Type 2 diabetes mellitus is a chronic disease that often causes complications of peripheral neuropathy in the form of decreased sensitivity of the legs. This condition increases the risk of diabetic leg injuries to amputation if prevention is not carried out early. One of the nonpharmacological interventions that can be carried out is Active Leg Stretching. This study aims to determine the effect of Active Leg Stretching on foot sensitivity in type 2 diabetes mellitus patients at the Tilongkabila Health Center. This study uses a pre-experimental design with a one group pretest–posttest approach. The study sample was a type 2 diabetes mellitus patient who experienced decreased sensitivity of the legs and was selected using the Purposive Sampling technique. Active Leg Stretching interventions were administered according to standard operating procedures during the study period. Leg sensitivity was measured using monofilament tests before and after the intervention. Data analysis was carried out using the Wilcoxon Signed Rank Test. The results showed an increase in foot sensitivity after being given an Active Stretching Leg intervention with a statistically significant difference (p-value < 0.05). This increase occurs because leg stretching can improve blood flow, reduce muscle stiffness, and improve nerve function, so the sensitivity of the legs increases. It can be concluded that Active Leg Stretching has a significant effect on increasing foot sensitivity in patients with type 2 diabetes mellitus. This intervention is recommended as a simple, safe, and easily applied nonpharmacological therapy in primary health care.